Toward an Understanding of why Suggestions Work in Charitable Fundraising: Theory and Evidence from a Natural Field Experiment - James T. Edwards; John A. List (Center for Economic Studies and ifo Institute (CESifo), 2013)
People respond to those who ask. Within the charitable fundraising community, the power of the ask represents the backbone of most fundraising strategies. Despite this, the optimal design of communication strategies has received less formal attention. For their part, economists have recently explored how communication affects empathy, altruism, and giving rates to charities. Our study takes a step back from this literature to examine how suggestions a direct ask for a certain amount of money affect giving rates. We find that our suggestion amounts affect both the intensive and extensive margins: more people give and they tend to give the suggested amount. Resulting insights help us understand why people give, why messages work, and deepen practitioners' understanding of how to use messages to leverage more giving.
Keywords: C93; 330